Linking experiencer-subject psych verb constructions in Modern Greek - Kordoni, Valia (The Proceedings of the 7th International Conference on Head-Driven Phrase Structure Grammar, 2001)
This paper focuses on the semantic properties and the syntactic behaviour of Modern Greek (hence MG) Experiencer-Subject Psych Verb Constructions (hence ESPVCs). MG ESPVCs include verbs like miso (hate), agapo (love), or latrevo (adore), which feature a nominative experiencer in agreement with the verb and an accusative theme (see examples (1)-(3)). MG ESPVCs include also predicates like fovame (fear), which feature an experiencer-subject in agreement with the verb and either an accusative theme (example (4)), or a theme as the object of a prepositional phrase (example (5)). We should underline here that examples (4) and (5) below convey the same meaning. That is, they do NOT differ semantically. O Gianis misi to sholio. the Gianis.N hate.3S the school.A "John hates school." O Gianis agapa tin Maria. the Gianis.N loves.3S the Maria.A "John loves Mary." O Gianis latrevi tin musiki. the Gianis.N adore.3S the music.A "John adores music." I Maria fovate tis kategides. the Maria.N fear.3S the storms.A "Maria is afraid of the storms." I Maria fovate me tis kategides. the Maria.N fear.3S with the storms.A "Maria is afraid of the storms." The challenge that constructions like the ones in (4) and (5) pose lies on the split syntactic realization of the "experienced" (hence EXPD) semantic role (i.e., the theme), which in constructions like (4) is syntactically realized as the object of the sentence, while in constructions like (5) it is syntactically realized as the object of a prepositional phrase. Our aim is to propose a unified linking account of the MG ESPVCs. This unified account is based on the assumption that the individual denoted by the object NP (or PP) of the MG ESPVCs is entailed to be semantically underspecified, and makes use of Wechsler's (1995) Notion Rule, Davis and Koenig's (2000) linking theory, as well as Markantonatou and Sadler's (1996) proposal for the linking of indirect arguments. References Davis, A.R. and J.-P. Koenig (2000). Linking as constraints on word classes in a hierarchical lexicon. Language 76, 56-91. Markantonatou, S. and L. Sadler (1996). Linking Indirect Arguments. Essex Research Reports in Linguistics 9, 24-63. Wechsler, S. (1995). The Semantic Basis of Argument Structure. Stanford: CSLI Publications. Series: Dissertations in Linguistics, Joan Bresnan, Sharon Inkelas, William J. Poser, and Peter Sells (eds.).